2022
DOI: 10.1002/app.53371
|View full text |Cite
|
Sign up to set email alerts
|

Flexible strain sensors with high sensitivity and large working range prepared from biaxially stretched carbon nanotubes/polyolefin elastomer nanocomposites

Abstract: Flexible strain sensors are a new generation of flexible and stretchable electronic devices that attracted increasing attention due to their practical applications in many fields. However, maintaining a wide detectable strain range while improving the sensitivity of flexible strain sensors remains challenging. In this study, flexible strain sensors with a large working range based on biaxially stretched carbon nanotubes (CNTs)/polyolefin elastomer (POE) nanocomposites were fabricated. Biaxial stretching was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…This further demonstrated that biaxial stretching could improve the secondary dispersion of the CNTs in the POE polymer, thus improving the sensitivity of strain sensors. 23,36 Compared with recently reported sensors, 9,10,12,21,23,[37][38][39][40][41] CNT/POE-POE strain sensors show greater advantages in sensitivity and monitoring range, which provides a good way to meet the requirements of a wider monitoring range and higher sensitivity (see Figure 8c).…”
Section: Sensing Performancementioning
confidence: 98%
See 4 more Smart Citations
“…This further demonstrated that biaxial stretching could improve the secondary dispersion of the CNTs in the POE polymer, thus improving the sensitivity of strain sensors. 23,36 Compared with recently reported sensors, 9,10,12,21,23,[37][38][39][40][41] CNT/POE-POE strain sensors show greater advantages in sensitivity and monitoring range, which provides a good way to meet the requirements of a wider monitoring range and higher sensitivity (see Figure 8c).…”
Section: Sensing Performancementioning
confidence: 98%
“…A DC digital source meter (Tektronix PWS4323) was used to provide power and the current was collected at a fixed voltage of 3 V through a picoampere-meter (Keithley 6485). The conductivity of nanocomposites was calculated by Equation 1 21 :…”
Section: Electrical Conductivitymentioning
confidence: 99%
See 3 more Smart Citations